Do gamblers understand complex bets? Evidence from Asian handicap betting on soccer - Tadgh Hegarty; Karl Whelan (University College Dublin, UCD School of Economics, 2023)
The Asian Handicap is a way to bet on soccer matches where payouts depend on an adjustment to the score that favors the weaker team. These bets are more complex than traditional betting on soccer because they require assessing the likely goal difference in the match rather than just the probabilities of a home win, away win or draw and because they can feature the possibility of all or half the bet being refunded. We show that bettors systematically lose more money on the type of Asian Handicap bets where refunds are not possible than they do when it is possible to obtain a half refund and that bets with the possibility of a full refund have the lowest loss rates. Bookmakers do not appear to adjust odds to equate the expected return on these bets. We show that the pattern of differences in loss rates across bets is predictable based on the odds quoted.
Keywords: G41; L83; 330; Pricing Complexity; Betting Markets; Asian Handicap